Development of clam shell derived hydroxyapatite reinforced epoxy based biomedical implant - Isiaka Oluwole Oladele; Samuel Olumide Falana; Vincent Andrew Akpan; Sumayyah Adejumoke Adenle; Linus Nnabuike Onuh (Discover Chemistry)
Abstract This study explores the impact of using hydroxyapatite (HAp) reinforcements obtained from clam shells on the mechanical and wear properties of epoxy-based composites. The main objective is to evaluate the suitability and effectiveness of these bio-composites for biomedical applications based on their properties. We collected waste from clam shells and processed it to obtain hydroxyapatite particles with a size of 45 μm. The hydroxyapatite-based epoxy composites were then created using the open mould stir-cast method, which involves mixing hydroxyapatite with epoxy resin and hardener before pouring the mixture into molds for curing. We conducted Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD) analyses on the hydroxyapatite particles obtained from clam shells and thoroughly assessed the mechanical and wear properties of the resulting composites. Furthermore, we examined SEM images of the fracture surfaces. The results revealed significant improvements achieved by incorporating hydroxyapatite derived from clam shells into the epoxy resin in the composites. We consistently achieved optimal values for various properties with a reinforcement content of 12–15 wt.%. At this weight fraction, the maximum flexural strength ranged from 41.40 to 61.31 MPa, hardness from 52.6 to 60.9 HRA, impact resistance from 14.37 to 15.91 J, and wear index from 0.04 to 0.08. These findings highlight the potential of these composites for applications in biomedical implants, prosthetics, and structural components in load-bearing environments. Graphical Abstract